Koordinasi Dinas Ketahanan Pangan Dalam Mengatasi Rawan Pangan Di Kelurahan Belawan Bahari Kota - Syafira Mulia Sari Pane; Rudi Kristian P.M (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The Medan City Government Resilience Service is responsible for the implementation of food which is structurally the authority of the Medan City Food Security Service. according to the main task and function, the Medan City Food Security Service must be able to empower all existing regional components/devices. Thus, with coordination among development actors, the implementation of food security in Medan City can be implemented successfully and efficiently. The research method used is descriptive qualitative. Techniques for collecting data were interviews, observations, and document recording. The data obtained are then analyzed by examining all the data that has been collected which is supported by the results of interviews with the effective coordination theory approach by Tripathi and Reddy (1994), namely direct relationships, initial opportunities, continuity, dynamism, clear goals, simple organization, formulation of authority and responsibility, effective communication, and effective supervisory leadership. The results of this study have not gone well. This is due to the inability of the Medan City Food Security Service to vary food, this program also causes dependence so that people do not have an effort to improve their nutrition, and the lack of supervision by the City of Medan so that there are people who misuse aid..